2015
DOI: 10.3906/sag-1312-132
|View full text |Cite
|
Sign up to set email alerts
|

Bioimpedance for assessing volume status in children with nephrotic syndrome

Abstract: Background/aim: The effectiveness of assessing volume load via bioimpedance in pediatric patients with nephrotic syndrome (NS) was investigated.Materials and methods: Patients with NS (n = 34) were compared with healthy controls (n = 20). The inferior vena cava index and inferior vena cava collapsibility index (IVCCI) scores were determined for all subjects. Bioimpedance measurements were used to directly determine volume load. Clinical findings, relative fluid load, and echocardiographic measurements were det… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
9
0
2

Year Published

2018
2018
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(13 citation statements)
references
References 25 publications
2
9
0
2
Order By: Relevance
“…In the present study, BIS clearly indicated a higher ECW in the ANS patients compared to both the controls (HC group) and patients at remission (NSR group). Importantly, these findings accord with observations made in previous studies in NS patients [4, 25], where absolute fluid volumes were estimated using predictive methods.…”
Section: Discussionsupporting
confidence: 91%
“…In the present study, BIS clearly indicated a higher ECW in the ANS patients compared to both the controls (HC group) and patients at remission (NSR group). Importantly, these findings accord with observations made in previous studies in NS patients [4, 25], where absolute fluid volumes were estimated using predictive methods.…”
Section: Discussionsupporting
confidence: 91%
“…However, data regarding the usage of bioelectrical impedance in nephrotic syndrome is limited. So far, bioimpedance technology has been used to estimate the fluid status of patients with nephrotic syndrome rather than body composition [18][19][20][21]. We decided to use this method to compare body composition in different groups of patients with kidney disease as simple tool which can be used at the patients' bedside.…”
Section: Discussionmentioning
confidence: 99%
“…The repeated measurements showed superior reproducibility of BCM-derived TBW estimates as compared to UKM-derived values, which is not surprising considering the simplicity of bioimpedance measurements as compared to the substantial biological and technical variation associated with a methodology requiring repeated blood sampling and laboratory measurements. The advantage of simplicity was also emphasised in a recent study comparing fluid status in children with nephrotic syndrome by bioimpedance and echocardiography [ 27 ].…”
Section: Discussionmentioning
confidence: 99%